Integrating extensive and intensive reading worksheets on digital platforms - Fahri Haswani; Yeni Erlita; Rika (JOALL (Journal of Applied Linguistics and Literature), 2023)
This study aims at exploring the strengths of extensive reading and intensive reading (EXIT) integration by involving the use of digital-platform base worksheet in optimizing the students’ reading skill. The foci include revealing the students’ perspectives towards such a hybrid implementation as well as theoretical justifications to the significances of EXIT integration and digital-platform base worksheet in reading activities. This descriptive qualitative study took place in a state university in North Sumatera ad involved 30 students of English education taking Writing class. Questionnaire, interview, and documentation were used to collect the data.  The qualitative data were then analyzed to meet triangulation data validity. It was found that the students perceive the significances of EXIT integration and roles of digital-platform base worksheet are oriented to optimize their reading comprehension. Documentation also showed the students’ interests and motivation in EXIT using digital-platform base improved. Exploration to teachers’ perspectives towards the same treatment is suggested to see the significances of each reading technique and reading tool from different point of view.